2018
DOI: 10.1111/jgh.14450
|View full text |Cite
|
Sign up to set email alerts
|

β‐Arrestin1 alleviates acute pancreatitis via repression of NF‐κBp65 activation

Abstract: β-Arr1 alleviates AP via repression of NF-κBp65 activation, and it is a potentially therapeutic target for AP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Actually, existing studies have reported that ARRB1 not only responds to the termination of G-protein activation as a classic adaptor protein but also participates in the mediation of the inflammatory response through multiple signal transduction pathways. Preceding research from our team revealed that ARRB1 alleviated acute pancreatitis via repression of NF-κBp65 activation [ 27 ]. A recent study showed that ARRB1 inhibited nonalcoholic steatohepatitis progression by promoting growth differentiation factor 15 maturation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, existing studies have reported that ARRB1 not only responds to the termination of G-protein activation as a classic adaptor protein but also participates in the mediation of the inflammatory response through multiple signal transduction pathways. Preceding research from our team revealed that ARRB1 alleviated acute pancreatitis via repression of NF-κBp65 activation [ 27 ]. A recent study showed that ARRB1 inhibited nonalcoholic steatohepatitis progression by promoting growth differentiation factor 15 maturation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Relative mRNA expression was normalized to the mRNA levels of β-actin (housekeeping control). 21,3136 Detailed primer sequences are shown in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Immunoreactivity was analysed using Western Lightening Plus enhanced chemiluminescence (PerkinElmer, MA, USA) according to the manufacturer's instructions. GAPDH was adopted as internal standard to control for unwanted sources of variation, and relative protein expression values were expressed as 'fold mean of the controls' by comparing with the corresponding control value, 32,[37][38][39][40] and the control value was normalized to 1.0.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…It has been demonstrated that nearly all pathways leading to NF-κB activation could be blocked by treatment with a variety of antioxidants, including N-acetyl-L-cysteine (NAC), glutathione (GSH), and thioredoxin (Mercurio & Manning, 1999 ). In recent years, a large number of active drugs have emerged to improve therapy for acute pancreatitis by inhibiting the NF-κB signaling pathway in experiments (Cen et al., 2016 ; Tao et al., 2019 ). Bilirubin is a bioproduct, and possessed potent antioxidant and anti-inflammatory properties (Yao, Jiang, et al., 2019 ; Yao, Jiang, 2019 ; Yao, Huang, 2020 ; Yao, Sun, 2020 ).…”
Section: Molecular and Cellular Mechanisms Of Acute Pancreatitismentioning
confidence: 99%